"Stand tall, turn your three guitars up real loud, and do what you do": The Redneck Liberation Theology of the Drive-By Truckers - Buma, Michael (Journal of religion and popular culture, 2006)
The relatively new genre of alternative country music often offers a similar theological perspective to that of its predecessor, traditional country. Both generally respond to the redneck condition-the plight of the rural working classes in the American South-by focussing on the immanent and material rather than the transcendent and spiritual. This paper will address alternative country's concern for the here-and-now as it occurs in the lyrics of one prominent band, the Drive-By Truckers. I will suggest that the Truckers subscribe to what David Fillingim has called "redneck liberation theology," a belief that the end to human suffering is due in the present world rather than in the promise of a distant heaven. The Drive-By Truckers ultimately find God and the organized church lacking in their ability to bring about human redemption, and, consequently, look to music as a surrogate "religion" that provides necessary, if provisional, spiritual answers.